Creating a British World: British colonial teachers and the Anglicising of Afrikaner children (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The contribution of the British Colonies in supporting Britain in its quest to promote English and British culture amongst Afrikaner children during and in theaftermath of the Anglo Boer War is examined in this article. A cursory background to the circumstances that shortly preceded the Anglo Boer War is provided to present the context of the study. Next, the role of the press in shaping opinions on an attitudes towards the key role players in the war is offered. This aspect is included since it points to how the opinions of British colony teachers who were recruited to teach Afrikaner children in South Africa had been shaped. This section is followed by an overview of concentration camp schools and an outline of the prevailing conditions of schooling at that time. Hereafter the experiences of teachers who had been recruited from each of three British Colonies - New Zealand, Canada and Australia – are presented. These experiences give the reader insight into how teaching occurred, what it comprised and how it was received by Afrikaner children who survived the concentration camps. This article aims to add to the body of knowledge on schooling during the time of the Anglo Boer War and the role that the British played in the provisioning of education. The article also outlines the attempts of the British to Anglicise Afrikaner youth. The research evidences that the explicit role of these teachers was to inculcate the English language and customs in Afrikanerchildren during and after the Anglo Boer War.
Keywords: Anglo Boer War; Anglicisation; British imperialism; Colonial teachers; Concentration camps; South African colonial schools; Colonial Australian teachers; Colonial New Zealand teachers; Colonial Canadian teachers